GENETIC TRANSFORMATION OF PLANTS CONTAINING THE SYNTHETIC cry1Ab GENE ENCODING RESISTANCE TO LEPIDOPTERAN PESTS - A. M. Taranenko; I. O. Nitovska; L. H. Velykozhon; P. D. Maystrov; M. V. Kuchuk; B. V. Morgun (Biotechnologia Acta, 2019)
The research was aimed to develop genetic constructs for Agrobacterium-mediated plant transformation, containing the synthetic cry1Ab gene, and their testing through the transformation of tobacco, followed by a molecular genetic analysis of the obtained plants to confirm the transformation event. Basic methods of DNA cloning, Agrobacterium-mediated transformation of Nicotiana tabacum L. by leaf disc method, selection of transformants in vitro, analysis of the transgene presence in plant DNA, detection of cry1Ab gene expression by PCR with reverse transcription were used. In the course of the study, the vectors pCB182 and pCB241 that contained the synthetic gene cry1Ab were constructed. Agrobacterium-mediated transformation of tobacco was carried out by created vectors and regenerant plants containing transgenes in their DNA were obtained. Expression of cry1Ab transgene in the obtained transformants of tobacco by the RT-PCR method was confirmed. As a result of the Agrobacterium-mediated transformation of plants with pCB182 and pCB241 vectors containing the synthetic cry1Ab lepidopteran resistance gene it is possible to obtain transgenic plants with expression of the transgene.